Treating Concomitant Language and/or Phonology Impairment in Children Who Stutter - Hall, Nancy E.; Singer, Cara M.; Sawyer, Jean (Seminars in Speech and Language, 2022)
Stuttering can co-occur with phonological and/or language impairment in a nontrivial number of children. This article provides a framework for addressing concomitant phonology/language impairment and stuttering through the application of the World Health Organization's International Classification of Functioning, Disability and Health (ICF) framework. Described is a multifactorial approach to understanding stuttering, the application of the ICF to treating children who stutter with concomitant disorders, and models for structuring-related therapy. A case study is explored to illustrate this process and includes a sample treatment plan with goals, short-term objectives, and sample activities.
Keywords: stuttering; children; concomitant disorder; treatment